Pengaturan Aspek Lingkungan Hidup dalam Perdagangan Internasional Berdasarkan GATT-WTO - Gustira, Zevia; Kusniati, Retno (Faculty of Law, Universitas Jambi, 2020)
International trade, in the era of globalization, is a method taken by state leaders to fulfill their domestic needs. The inability of a country to meet this need, interests often friction. It is not uncommon for the State to take action that can harm other countries. Excessive exploitation of domestic natural resources, international awareness in the sustainability of natural resources, about protecting resources and even creating sustainability to enjoy these natural resources. The seriousness of the international world can also be seen from the steps taken by world leaders, the format of changing GATT which only pays attention to the protection of its member countries in conducting international trade with other countries can be protected, as well as members of developing countries and poor countries. The next development of awareness that the environment could be threatened by exploitation, it was the WTO that was formed to perfect GATT International trade, in the era of globalization, is a method taken by state leaders to fulfill their domestic needs. The inability of a country to meet this need, interests often friction. It is not uncommon for the State to take action that can harm other countries. Excessive exploitation of domestic natural resources, international awareness in the sustainability of natural resources, about protecting resources and even creating sustainability to enjoy these natural resources. The seriousness of the international world can also be seen from the steps taken by world leaders, the format of changing GATT which only pays attention to the protection of its member countries in conducting international trade with other countries can be protected, as well as members of developing countries and poor countries. The next development of awareness that the environment could be threatened by exploitation, it was the WTO that was formed to perfect GATT.